Anthroposophic Medicinal Products: A Literature Review of Features, Similarities and Differences to Conventional Medicinal Products, Scientific and Regulatory Assessment. (10th January 2022) - Baars, Erik W.; Kienle, Gunver S.; Heusser, Peter; Pedersen, Peter A.; Wietmarschen, Herman A. van; Kiene, Helmut; von Schoen-Angerer, Tido; Hamre, Harald J.
Background: Regulatory assessment of anthroposophic medicinal products (AMPs) can be challenging due to their specific features. Objective: The aim of this paper is therefore to provide adequate scientific information on AMPs for regulatory purposes. Methods: A literature review was executed with database searches in PubMed, Cinahl, Merkurstab, Anthromedics, andhttps://iaap-pharma.org/ . Search terms were: anthroposophic medicinal products, anthroposophic medicines, anthroposophic pharmacy. There was no language restriction; searches were executed from onset until June 11, 2020. In addition, experts were invited to suggest relevant literature. Results: Eighty-seven of 660 identified publications were included. The system of anthroposophic medicine (AM) with its conceptual background and various aspects of AMPs was described: definition, pharmaceutical properties, an example of AMP development, use in clinical practice, similarities with and differences to conventional medicinal products, societal aspects, scientific and regulatory assessment. Conclusion: AMPs are part of the integrative whole medical system of AM. AMPs are manufactured according to Good Manufacturing Practice and national drug regulations and have an excellent safety status; the limited available evidence suggests clinical benefits. Current drug regulation of AMPs in the EU and most European countries does not take the special properties of AMPs into account. Future research should focus on appropriate methodologies for the evaluation of effects of AMPs as part of the AM whole medical system, the scientific quality of its non-atomistic holistic ontological position, and the integration of AM and conventional medicine in clinical practice. Future policies should focus on appropriate ways of addressing regulatory challenges to AMPs.